CURRICULUM DEVELOPMENT IN IMPROVING STUDENTS’ ISLAMIC CHARACTER - Syah, Mohamad Hakiki (State Institute of Islamic Studies (IAIN) Palu, 2019)
Curriculum development in improving Islamic character becomes a focus of attention in schools, especially schools with Islamic nuance in an effort to build Islamic students. The inclusion of this Islamic character development aims to produce graduates who have moral values that uphold Islamic values that have a commendable attitude in society, good discipline, honest, independent, and other positive attitudes that are embedded in students. This research is field research that serve the data with analytical analysis. The study used psychological and sociological approach. The result found the inclusion of Islamic character, such as faith and piety, honesty, trustworthy, fair, responsible, sympathetic, political and others, in the curriculum development.